PERAN PEREMPUAN DALAM UPAYA PENYELESAIAN KONFLIK: STUDI KASUS GERAKAN PEREMPUAN DALAM KONFLIK ISRAEL-PALESTINA - Al Usman, Shakira Aulia (Jurnal Polinter : Kajian Politik dan Hubungan Internasional, 2025)
The protracted Israeli-Palestinian conflict has been in the international spotlight since the Balfour declaration in 1917. In this conflict, Palestinian women have played an important role in peace efforts and conflict resolution. In this analysis, we examine the role, strategy, and contribution of Palestinian women in resolving the conflict using peace approaches, non-violent conflict resolution theories, and feminist theories. This study uses a qualitative approach with descriptive analysis to describe the phenomenon of women's participation in conflict resolution. Data were collected through literature studies and secondary data through literature studies. Palestinian women have been actively involved in nonviolent resistance movements, such as peaceful demonstrations, campaigns, and dialogue, in an effort to achieve peace. They also play a role in children's education about nonviolent resistance and political awareness. In addition, women play an important role in socio-economic activities, such as establishing alternative education systems, food cooperatives, and providing humanitarian assistance. Through this analysis, it is hoped that a broader understanding of the role of women in resolving the Israeli-Palestinian conflict, as well as recognition of the importance of women's participation in promoting peace and justice in the world.